Investigation of Band Structure of ZrNiSn1-xGax Semiconductor Solid Solution - Romaka, L.P.; Stadnyk, Yu.V.; Romaka, V.V.; Krayovsky, V.Ya.; Rogl, P.-F.; Нoryn A.M. (Physics and Chemistry of Solid State, 2017)
The mechanism of simultaneous generation of donor-acceptor pairs in ZrNiSn1-xGax semiconductor solid solution is established. The modeled distribution of atoms in the crystal lattice of ZrNiSn1-xGax showed that the speed of movement of Fermi level εF, obtained from the band structure calculations is in agreement with experimental extracted from lnρ(1/T) dependencies. It is shown that with substitution of Sn (5s25p2) with Ga (4s24p1) atoms in 4b crystallographic site both acceptor and donor (vacancies in 4b site) defects are generated.